2020
DOI: 10.18806/tesl.v37i2.1335
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Feedback and Multimodality: Rethinking Categories in Telecollaborative Learning

Abstract: Teletandem (Telles, 2009) is a model of telecollaboration in which pairs of foreign language students from different countries meet regularly and virtually to learn each other’s languages. Within this context, participants are expected to help their partners learn by providing feedback. The multimodal nature of this type of environment, however, may offer different learning opportunities (Guichon & Cohen, 2016) and have an impact on feedback provision. This research aims at investigating peer corrective fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…These insights from different theoretical perspectives are essential to understand research results found in bilingual telecollaborative language learning settings, like teletandem. Studies on (tele)tandem settings (AKIYAMA, 2013;FRESCHI, 2017;FRESCHI;CAVALARI, 2020) revealed that, because participants take turns during the oral interaction, performing the role of the learner of a foreign language and the role of the tutor of their own native language, they seem to establish a symmetrical, empathic and collaborative relationship which may have an impact on feedback provision. Capellini, Elstermann, and Monpean (2020), who examined how 46 teletandem participants experience reciprocity in the teletandem setting, revealed that this principle is related to trying to meet the partner's learning needs and correction is considered one way to do that.…”
Section: Metalinguistic Cluementioning
confidence: 99%
See 4 more Smart Citations
“…These insights from different theoretical perspectives are essential to understand research results found in bilingual telecollaborative language learning settings, like teletandem. Studies on (tele)tandem settings (AKIYAMA, 2013;FRESCHI, 2017;FRESCHI;CAVALARI, 2020) revealed that, because participants take turns during the oral interaction, performing the role of the learner of a foreign language and the role of the tutor of their own native language, they seem to establish a symmetrical, empathic and collaborative relationship which may have an impact on feedback provision. Capellini, Elstermann, and Monpean (2020), who examined how 46 teletandem participants experience reciprocity in the teletandem setting, revealed that this principle is related to trying to meet the partner's learning needs and correction is considered one way to do that.…”
Section: Metalinguistic Cluementioning
confidence: 99%
“…In the Teletandem setting as implemented at UNESP, PCF of oral production has been examined by Benedetti and Gianini (2010), Freschi (2017), Cavalari and Freschi (2018), Freschi and Cavalari (2020) and Pereira Filho (ongoing). Benedetti and Gianini (2010) studied how a Brazilian (Spanish learner) provided feedback to an Argentinian (Portuguese learner).…”
Section: Metalinguistic Cluementioning
confidence: 99%
See 3 more Smart Citations